Effectiveness of osteotropic material Easy-Graft according morphological analysis in experiment and for the assessment of life quality in patients with generalized periodontitis І severity level - Dmitrieva E.O. (Морфологія, 2013)
Background. The theoretical basis of osteoplasty, fully supported by clinical observations, is that violations occur in periodontitis of correlation between tooth and the surrounding tissues, including the microcirculation. However, complex morphological and clinical analysis of effectiveness of the material held EasyGraft was not. Objective. The aim was experimental evaluation of tissue alterations in bone implant materials Easy-Graft® and tricalcium phosphate®, as well as determining the life quality after use in the surgical treatment of patients with generalized periodontitis І severity level. Methods. The comparative analysis a quantitative morphological estimation of regenerative processes in osteal tissue in model of osteal defect is carried out at implantation of material EasyGraft and amorphous calcium phosphate at this work. It was investigated dynamics of life quality indicators at patients after used materials by specialised questionnaire OHІР-14 during 1 year. Results and Conclusion. We found out that EasyGraft and amorphous calcium phosphate undergo resorbtion and thus optimize bone regeneration. Regeneration is accompanied by decreased specific area of the particles implanted and increased integration index and specific density of trabeculae within the reaction zone. Highest intensity of these processes was ob-served in the period from 15th fill the 30th day after implantation. EasyGraft is more preferable for implantation than amorphous calcium phosphate. Adapted Ukrainian language and Russian language version of the OHIP-14 questionnaire (Oral Health Impact Profile) is valid and accurate tool for assessing the quality of life of patients with chronic generalized periodontitis by which demonstrated the influence of the intensity of inflammatory and destructive changes periodontal severity of the pathological process, the presence of complete occlusion and methods of correction applied to the subjective perception of quality of life. The use of material EasyGraft compared with tricalcium phosphate improves the life quality of patients by 18-20 %.